2017
DOI: 10.1038/nature24453
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the heavy elements in binary neutron-star mergers from a gravitational-wave event

Abstract: The cosmic origin of elements heavier than iron has long been uncertain. Theoretical modelling shows that the matter that is expelled in the violent merger of two neutron stars can assemble into heavy elements such as gold and platinum in a process known as rapid neutron capture (r-process) nucleosynthesis. The radioactive decay of isotopes of the heavy elements is predicted to power a distinctive thermal glow (a 'kilonova'). The discovery of an electromagnetic counterpart to the gravitational-wave source GW17… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

82
1,203
3
36

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,150 publications
(1,344 citation statements)
references
References 66 publications
82
1,203
3
36
Order By: Relevance
“…The light-curve properties were interpreted as being produced by dynamical ejecta from the merger and secular ejecta from the merger remnant. The estimated ejecta mass is in the range 0.03 to 0.05 M (Cowperthwaite et al 2017;Kasen et al 2017;Nicholl et al 2017;Chornock et al 2017;Drout et al 2017;Smartt et al 2017;Kasliwal et al 2017;Kilpatrick et al 2017;Tanvir et al 2017;Tanaka et al 2017), which even for asymmetric binaries lies near the high end of the theoretical range expected from simulations. This can be interpreted as tentative evidence for a delayed/no collapse in GW170817 because this merger outcome tends to produce larger ejecta masses as compared to a direct collapse (Bauswein et al 2013b;Hotokezaka et al 2013;Fernández & Metzger 2013;Metzger & Fernández 2014;Perego et al 2014;Siegel et al 2014;Wanajo et al 2014;Just et al 2015;Sekiguchi et al 2016).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The light-curve properties were interpreted as being produced by dynamical ejecta from the merger and secular ejecta from the merger remnant. The estimated ejecta mass is in the range 0.03 to 0.05 M (Cowperthwaite et al 2017;Kasen et al 2017;Nicholl et al 2017;Chornock et al 2017;Drout et al 2017;Smartt et al 2017;Kasliwal et al 2017;Kilpatrick et al 2017;Tanvir et al 2017;Tanaka et al 2017), which even for asymmetric binaries lies near the high end of the theoretical range expected from simulations. This can be interpreted as tentative evidence for a delayed/no collapse in GW170817 because this merger outcome tends to produce larger ejecta masses as compared to a direct collapse (Bauswein et al 2013b;Hotokezaka et al 2013;Fernández & Metzger 2013;Metzger & Fernández 2014;Perego et al 2014;Siegel et al 2014;Wanajo et al 2014;Just et al 2015;Sekiguchi et al 2016).…”
Section: Observationsmentioning
confidence: 99%
“…Our constraint only relies on the measured binary mass of GW170817 and the evidence for a delayed/no collapse in this event as suggested by its electromagnetic emission (e.g. Kasen et al 2017;Metzger 2017). In the case of a delayed/no collapse the measured total binary mass of GW170817 provides a lower bound on the threshold mass for direct BH formation,…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the opposite view of interpreting the blue component as due to the dynamical ejecta exists in the literature (e.g. Kasen et al 2017;Nicholl et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The optical/IR counterpart of GW170817 indeed showed two distinct blue and red components (Evans et al 2017;Drout et al 2017;Nicholl et al 2017;Smartt et al 2017;Arcavi et al 2017;Kasen et al 2017;Cowperthwaite et al 2017;Kilpatrick et al 2017;Villar et al 2017). Fitting the light curve, one could obtain the properties for both components, such as their velocities, opacities, and especially the masses of the two components.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48]. Furthermore the measurements of the EM redshift and, from the GW signal, the luminosity distance, allowed an independent estimate of the Hubble constant to be made [49], thus demonstrating a thirty year old prediction [50].…”
Section: Introductionmentioning
confidence: 99%